Change and Stability in the Characteristics of Homicide Victims, Offenders and Incidents During Rapid Social Change - Pridemore, William Alex (The British journal of criminology, 2007)
The Russian homicide rate doubled during the 1990s and is now among the highest in the world. During this same period, Russian citizens experienced swift, widespread, and meaningful political, economic, and social change. It is likely that this profound transition altered structural conditions, cultural norms, and interpersonal relations in a way that led to changes in the nature of interpersonal violence. Taking advantage of a unique set of homicide narratives drawn from court and police records in the Udmurt Republic, this study examined stability and change in the distribution of Russian homicide victim, offender, and incident characteristics before and after the fall of the Soviet Union. Odds ratios obtained from logistic regression showed no change in victim characteristics, but substantial changes in several offender and incident characteristics. We discuss the potential mechanisms through which the structural and cultural shifts are resulting in these changes and conclude that the ongoing transition is largely responsible for the changing nature of homicide in Russia. In doing so, we introduce the new term "criminological transition" and suggest that Russia (and perhaps other nations) may have experienced a change in its crime profile in much the same way as we discuss a "demographic transition" in terms of fertility and mortality profiles